2008
DOI: 10.1111/j.1464-410x.2008.07661.x
|View full text |Cite
|
Sign up to set email alerts
|

Enucleation of renal cell carcinoma with ablation of the tumour base

Abstract: OBJECTIVE To retrospectively assess the effectiveness of cancer control with enucleation of renal cell carcinoma (RCC), which is surgically expedient, allows preservation of maximal renal parenchyma, and makes intraoperative renal ischaemia unnecessary, by two surgeons routinely enucleating renal tumours and ablating the tumour bed with argon beam and the Nd‐YAG laser. PATIENTS AND METHODS Between 1996 and 2006 at our institution, 97 patients had RCC enucleated, with ablation of the tumour base. Patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…In this scenario, some studies have supported the oncological efficacy of the simple enucleation (SE) technique, defined as the blunt excision of the tumor without a visible margin, following the natural cleavage plane between the tumor capsule and healthy parenchyma. Prospective studies confirmed the SE safety from a pathological perspective [3] and large retrospective series showed its oncological equivalence to standard PN [4][5][6].Data from the largest comparative study between open PN (OPN) and laparoscopic PN (LPN) found LPN to be a Electronic supplementary material The online version of this article ( …”
mentioning
confidence: 84%
“…In this scenario, some studies have supported the oncological efficacy of the simple enucleation (SE) technique, defined as the blunt excision of the tumor without a visible margin, following the natural cleavage plane between the tumor capsule and healthy parenchyma. Prospective studies confirmed the SE safety from a pathological perspective [3] and large retrospective series showed its oncological equivalence to standard PN [4][5][6].Data from the largest comparative study between open PN (OPN) and laparoscopic PN (LPN) found LPN to be a Electronic supplementary material The online version of this article ( …”
mentioning
confidence: 84%
“…Overall, many large series with single sporadic RCC treated conservatively by either standard partial nephrectomy or TE reported favorable survival and recurrence rates, but tumor progression may occur in some cases [2,[4][5][6][7][9][10][11][12]. This evidence has led to identifying clinical and pathological parameters as predictors of disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…The recent European Association of Urology guidelines expanded its indication for solitary renal cell carcinoma (RCC) up to a diameter of 7 cm, whenever technically feasible. A minimal tumor-free surgical margin appears appropriate to avoid the risk of local recurrence, thus supporting the possible use of the tumor enucleation (TE), which is a nephron-sparing procedure with oncological effectiveness supported by numerous papers (Level of Evidence 2b) [1][2][3][4][5][6][7][8]. Over the past years, this technique has received a wider consensus as an alternative to standard partial nephrectomy for T1 RCC and has been adopted in several centers [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several retrospective studies have confirmed good oncologic results of SE and some of these studies have demonstrated also a similar local recurrence-free survival and cancer specific survival rates between SE and standard PN, for renal tumors with clinical diameter up to 7 cm; one study have also confirmed similar cancer specific survival between SE and radical nephrectomy [18][19][20][21][22][23][24][25].…”
Section: Surgical Margin Statusmentioning
confidence: 85%